Protocole d’errance d’une forme - Francesca Cozzolino; Coralie Maurin; Kristina Solomoukha (Ateliers d'Anthropologie)
This text looks back at the developmental stages of an animated short film that grew out of image-based research into Zapatista iconography, grounded in an ethnographic investigation in Chiapas. Designed by an anthropologist, an artist, and a filmmaker, this audio-visual narrative is built like a virtual trip through different groups of images in which different variants of the caracol are shown—a motif that, ranging from the representation of the snail shell to the spiral, embodies both the Maya past and the Zapatista ideals of the present. We present the way this film took shape through an interactive device that serves as a script, as well as the aesthetic choices and narrative principles adopted to configure this research conceived as a sensory experience opening several heuristic and speculative paths through collection of images.